Immune function in newborns with in-utero exposure to anti-TNFα therapy - Weiss, Batia; Ben-Horin, Shomron; Lev, Atar; Broide, Efrat; Yavzori, Miri; Lahat, Adi; Kopylov, Uri; Picard, Orit; Eliakim, Rami; Ron, Yulia; Avni-Biron, Irit; Yerushalmy-Feler, Anat; et al. (Frontiers in Pediatrics, 2022)
Background and aim: Anti-TNFα is measurable in infants exposed in-utero up to 12 months. Data about the exposure effect on the infant's adaptive immunity are limited. We aimed to evaluate prospectively the distribution and function of T and B cells, in infants of females with inflammatory bowel disease, exposed to anti-TNFα or azathioprine in-utero. Methods: A prospective multi-center study conducted 2014-2017. Anti-TNFα levels were measured in cord blood, and at 3 and 12 months. T-cell repertoire and function were analyzed at 3 and 12 months by flow-cytometry, expression of diverse T cell receptors (TCR) and T-cell receptor excision circles (TREC) quantification assay. Serum immunoglobulins and antibodies for inactivated vaccines were measured at 12 months. Baseline clinical data were retrieved, and 2-monthly telephonic interviews were performed regarding child infections and growth. Results: 24 pregnant females, age 30.6 (IQR 26.5-34.5) years were recruited, 20 with anti-TNFα (infliximab 8, adalimumab 12) and 4 with azathioprine treatment. Cord blood anti-TNFα was higher than maternal blood levels (4.3 (IQR 2.3-9.2) vs. 2.5 (IQR 1.3-9.7) mcg/ml), declining at 3 and 12 months. All infants had normal number of B-cells (n=17), adequate levels of immunoglobulins (n=14), and protecting antibody levels to Tetanus, Diphtheria, Hemophilus influenza-B and hepatitis B (n=17). All had normal CD4+, CD8+ T-cells and TREC numbers. TCR repertoire was polyclonal in 18/20 and slightly skewed in 2/20 infants. No serious infections were recorded. Conclusions: T-cell and B-cell immunity is fully mature and immune function is normal in infants exposed in utero to anti-TNFα as in those exposed to azathioprine.